ملامح التّوليد في التّراث اللّغويّ - ألبب إبراهيم (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يتناول البحث قضيّة من القضايا الهامّة الّتي يقوم عليها تراثنا اللغويّ، وقد جاءت متناثرة في كتب التّراث من دون ضابط يضبطها، أو قانون يحكمها. وهي مع أهمّيّتها لم تُعْطَ حقّها من الدّراسة والبحث. فمبدأ التّوليد يتيح للغة الاستمرار في التّعبير والتتابع في الألفاظ والتّراكيب والمعاني؛ وذلك من خلال إنتاج جملٍ لا حصر لها من مجموعة من الألفاظ والرّموز الكتابيّة المحدودة. ولغتنا العربيّة تقوم على ذلك، ويمكن أن نرى ملامح هذا التّوليد فيها على أربعة أشكال، هي: - التّوليد الوضْعيّ: وفيه بيان لملامح التّوليد القائم على وضع اللغة في حروفها وكلماتها المعجميّة وأفعالها وأسمائها خارج السّياق الّذي ترد فيه. - التّوليد السّطحيّ: وفيه يظهر الأثر الموقعيّ للمفردات بناء على تأثير عامل من العوامل. ويكون ذلك في مجال النّحو، والصّرف، واللغة، والأصول. - التّوليد التّحويليّ: ومفاده أنّ اللغة تتولّد فيها مفرداتٌ وتراكيب بناء على تحويل في مستوى الصّوت أو الصّرف أو النّحو أو الضّرورة الشّعريّة أو قواعد الرّتبة أو الحذف أو الزّيادة. - التّوليد الدّلاليّ: ويبحث في الدّلالات والمفاهيم الّتي تولّدها مفردات اللغة وتراكيبها. وهو مبنيّ على الحمل على المعنى والأدوات والجمل وبعض قضايا الصّرف وفقه اللغة. وهذه الأنواع مبثوثة في تراثنا اللغويّ تحت مسمّيات ومصطلحات مختلفة في ألفاظها واحدة في معناها. وإذا كان القدماء لم يسمّوها كما يسمّيها اليوم علم اللغة الحديث فإنّهم قصدوها في كتاباتهم، وأقاموا عليها لغتهم، وحافظوا من خلالها على استمرارهم. This study deals with one of the important questions upon which our linguistic heritage depends: generation. It had sporadically been addressed in our classical books, but none tried to regulate it or set the rules governing it. Despite its importance, it has not been given its due of analysis and research. The principle of generation makes it possible for language to continue producing new expressions, vocabulary, structures, and meanings out of a limited group of written words and symbols. Arabic is based on such generative principle that can take four shapes: Basic generation: This type of generation depends on dictionary language: letters, words, verbs and nouns out of context. Superficial generation: It shows the effect of the words’ position based on any factor in relation to grammar, morphology, and roots. Transformational generation: This means the generation of vocabulary and structures based on transformation at the levels of sounds, morphemes, grammar, poetic license, inversion and the rules of addition or omission. Connotative generation: This discusses the connotations and concepts generated by language vocabulary and structures. It is based on associations of meanings, articles, sentences and some other issues related to morphology and philology. These types of generation are there in our linguistic heritage and take a variety of names and idioms that have one meaning. Even though past writers did not give them the names given to them today by modern linguistics, they meant them in their writings, made their language depend on them, and maintained their continuity through them.